A STUDY OF NORMATIVE AND ANTHROPOLOGICAL APPROACHES TO THE BARZANJI TRADITION IN CHILD BIRTH CEREMONIES - Muhammad Ilham; Ivahni Ivahni (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
Islamic studies covers a variety of different meanings, divisions and aspects. However, the main focus of this study is on Islamic teachings which originate from the Koran and Hadith authentically. Therefore, it is necessary to use the right approach in understanding Islam. In this research, the author used two approach methods. Namely Normative and Anthropological. In the Big Indonesian Dictionary, tradition is a tradition or custom passed down from generation to generation that was passed down by ancestors and is still preserved by the community. One of the community traditions that is still highly preserved is the ceremony to welcome the birth of a child or often called akikah. One of the Islamic traditions carried out to welcome the birth of a child is Barzanji. This tradition originates from Arab countries and is generally spread through trade and marriage. The aim of the Barzanji tradition is to bring closer relations with Allah, increase faith and love for the Messenger of Allah, as a symbol of the Islamic religion and remind the history of the life of the Prophet SAW so that he becomes a role model, strengthen Islamic brotherhood among the community and maintain Islamic culture in the face of non-Islamic culture. who enter society.